Effect of different adhesive strategies on microtensile bond strength of computer aided design/computer aided manufacturing blocks bonded to dentin - Renato Roperto; Anna Akkus; Ozan Akkus; Lisa Lang; Manoel Damiao Sousa-Neto; Sorin Teich; Thiago Soares Porto (Wolters Kluwer Medknow Publications, 2016)
Background: The aim of this study was to determine the microtensile bond strength (μTBS) of ceramic and composite computer aided design-computer aided manufacturing (CAD-CAM) blocks bonded to dentin using different adhesive strategies. Materials and Methods: In this in vitro study, 30 crowns of sound freshly extracted human molars were sectioned horizontally 3 mm above the cementoenamel junction to produce flat dentin surfaces. Ceramic and composite CAD/CAM blocks, size 14, were sectioned into slices of 3 mm thick. Before bonding, CAD/CAM block surfaces were treated according to the manufacturer's instructions. Groups were created based on the adhesive strategy used: Group 1 (GI) - conventional resin cement + total-etch adhesive system, Group 2 (GII) - conventional resin cement + self-etch adhesive system, and Group 3 (GIII) - self-adhesive resin cement with no adhesive. Bonded specimens were stored in 100% humidity for 24h at 37΀C, and then sectioned with a slow-speed diamond saw to obtain 1 mm × 1 mm × 6 mm microsticks. Microtensile testing was then conducted using a microtensile tester. μTBS values were expressed in MPa and analyzed by one-way ANOVA with post hoc (Tukey) test at the 5% significance level. Results: Mean values and standard deviations of μTBS (MPa) were 17.68 (±2.71) for GI/ceramic; 17.62 (±3.99) for GI/composite; 13.61 (±6.92) for GII/composite; 12.22 (±4.24) for GII/ceramic; 7.47 (±2.29) for GIII/composite; and 6.48 (±3.10) for GIII/ceramic; ANOVA indicated significant differences among the adhesive modality and block interaction (P < 0.05), and no significant differences among blocks only, except between GI and GII/ceramic. Bond strength of GIII was consistently lower (P < 0.05) than GI and GII groups, regardless the block used. Conclusion: Cementation of CAD/CAM restorations, either composite or ceramic, can be significantly affected by different adhesive strategies used.